Köp av sexuell tjänst på distans - Gonzalez Spennare,Hannah (2023)
This thesis explores the possibilities of committing the crime purchase of sexual service remotely. The investigation begins with a closer examination of the offense itself. It is noted that the punishable act “casual sexual relation in return for payment”, is closely related to the abolished term “sexual intercourse”. The crimes in chapter six in the Swedish Criminal Code that currently can be committed remotely are linked to the newer term “sexual act”. Consequently, a comparison is made between the term “sexual intercourse” and the term of “sexual act”. Through this comparison, differences and similarities emerge. This comparison is further analyzed in relation to how the Supreme Court assessed the possibility to remotely commit these crimes before it was explicitly stated. Based on the investigation conducted in the essay, nothing indicates that the terminological difference between sexual intercourse and sexual act constitute an obstacle to committing the crime of purchasing sexual services remotely.
Keywords: Straffrätt; Criminal law; Sexualbrott; Köp av sexuell tjänst; Distansbestämmelsen